Women Courageous Leading Through the Labyrinth. - Moss Breen, Jennifer (Emerald Publishing Limited, 2021)
Women Courageous: Leading through the Labyrinthis a unique collection of stories of courage, integrated with scholarly analysis to deepen our understanding of courage - how it shows up, develops, and facilitates transformation.